STRATEGI PROMOSI DALAM MENINGKATKAN PENJUALAN PRODUK UNGGUL “NPK PUSRI“ DI PT PUPUK SRIWIDJAJA PALEMBANG - Meisa Priantika; Efan Elpanso (Bajang Institute, 2024)
Pupuk Indonesia has a commitment to support food security in this country. This led Pupuk Indonesia to transform into a complete and integrated agricultural solution provider. In increasing interest in innovation within Pupuk Indonesia, innovation must be part of KPIs up to the work unit level. By designing and executing promotional strategies through socialization well, PT Pupuk Sriwidjaja Palembang can strengthen its brand image, increase sales, and build better relationships with customers and other stakeholders. This study used a qualitative approach with observation and interviews. Based on the research that the author conducted, the conclusion of promotional activities by means of socialization plays an important role in creating brand awareness of PT Pupuk Sriwidjaja Palembang among potential customers and the general public. By demonstrating their products or services live, companies can give audiences a real experience of the value and benefits they offer.